Investigating The Term of “Concept” In Modern Linguistics - Alıyeva, Gunay Dilgem (Advances in Social Sciences Research Journal, 2017)
The term concept was first used by A. Aleksev. Then the term of concepts are used in different linguistic fields. In particular, concept is considered to be very important in the development of a wide range of cognitive linguistics. The concept is characterized by various types of linguists. Our studies prove that the concepts are formed in the human brain. According to the scientists in the minds of every person a concept exists as a man sees, or hears and so on. Some specific knowledge about events and things happen in the world may appear in the mind of every person who was born. While people talk, or think, or do something in any other situations concepts are exercised by them. For example, we may use some concepts in such a situation that even ourselves cannot imagine that how such kind of concept appears in our minds. Some scientists define such kinds of conceptual behavior acts a human’s mind. This is a case that arose in relation to concepts in our minds.